Xpert MTB/RIF assay for the diagnosis of Mycobacterium tuberculosis and Rifampicin resistance in high Human Immunodeficiency Virus setting in Gambella regional state, southwest Ethiopia. (August 2018) - Ejeta, Eyasu; Beyene, Getenet; Bonsa, Zegeye; Abebe, Gemeda
Abstract: Background: The introduction of a new and rapid molecular diagnostic for tuberculosis (TB) and rifampicin resistance (RIF) in the national TB program has improved the diagnosis of TB by shortening the turnaround time and detecting the presence of RIF resistance in high TB and human immunodeficiency virus (HIV) settings such as Ethiopia. However, the implementation of this new diagnostic tool for the diagnosis of M. tuberculosis (MTB ) and rifampicin (RIF) resistance in clinical setting is limited known in the country. Hence, this study intended to describe the program of GeneXpert MTB/RIF in the diagnosis of TB and RIF in high HIV setting in Gambella Regional State, Southwest Ethiopia. Method: Institutional based retrospective study was conducted among presumptive TB patients diagnosed with GeneXpert assay in the last three years (2015–2017) in Gambella Hospital from May 1–30, 2017. The data were collected from GeneXpert registration book using standard data extraction sheet. The data were entered and cleared using EPI data 3.1 and then, exported and analyzed using SPSS version 20.0 statistical software package. Result: Of the 995 presumptive TB patients who received the GeneXpert test in the last three years, 20.0% (95% CI: 17.4–22.7) of them had proven MTB detection while 4.9% (95% CI: 2.2–8.1) had RIF resistance. The prevalence of RIF resistance was 2.3% and 14.3% among the new and retreated cases respectively. There was also a 35.5% TB/HIV co-infections. The odd of MTB detection was higher among 15–29 [AOR 2.17 (95% CI: 1.25- 3.76)] and 30–44 [AOR 2.35 (95% CI: 1.36–4.07)] year old participants. The figure was however significantly lower among female [AOR 0.64 (95% CI: 0.45–0.91)] and unknown HIV status [AOR 0.38(95% CI: 0.24–0.61)] participants of the study. In addition, the odd of RIF resistance was significantly low among HIV unknown case [AOR 0.14 (95% CI: 0.02–0.96)]. It was also learnt that there was progressively decline of invalid or error Xpert result from 4.7% to 2.0% in the course of the study period (X 2, 25.54; P = 0.001). Conclusion: The study confirms the high prevalence of TB, RIF resistance and TB/HIV co-infection among the study participants. Age, sex, and HIV status of the study participants were predictor factors for MTB detection while HIV status was associated with RIF resistance. Therefore, the results of the study indicate that there is the need for collaborative and intensified prevention of TB and HIV in the study area. The ongoing supervision and mentoring to improve the performance of Xpert in the institution need to be promoted.